The Risk Factors for Diabetic Retinopathy in a Chinese Population: A Cross-Sectional Study - Qingmin Sun; Yali Jing; Bingjie Zhang; Tianwei Gu; Ran Meng; Jie Sun; Dalong Zhu; Yaping Wang (Journal of Diabetes Research)
Aims. Epidemiological data on diabetic retinopathy (DR) in Chinese population is still rather scarce, and risk factors for diabetic retinopathy are inconsistent because of study designs, grading standards, and population samples. Materials and Methods. This hospital-based retrospective study included 1052 type 2 diabetes patients. Diabetic retinopathy was diagnosed by nonmydriatic fundus photography and/or fundus examination apparatus. Logistic regression analysis was performed to evaluate the risk of diabetic retinopathy. Results. A total of 352 (33.5% prevalence) subjects were diagnosed with diabetic retinopathy based on our population. The patients in the DR group not only had significantly higher hemoglobin A1c (HbA1c), fasting plasma glucose (FPG), urinary microalbumin-creatinine ratio (ACR), and systolic blood pressure but also had higher follicle-stimulating hormone (FSH), luteinizing hormone (LH), and sex hormone-binding globulin (SHBG) levels compared to those in the non-DR group. Moreover, we confirmed that diabetes duration and HbA1c are strongly associated with DR risk. We also found that serum LH was an independent risk factor in male diabetic retinopathy patients (OR=1.086, 95% CI 1.024–1.152), and the levels of LH were significantly associated with diabetic retinopathy prevalence (P=0.018). Conclusions. Our study strengthens the argument that diabetes duration and HbA1c are risk factors for patients with DR. Additionally; we firstly confirmed that serum LH was an independent risk factor in male diabetic retinopathy patients.